The thinking on controversy of "1-year rule" for differential diagnosis between Parkinson's disease dementia and dementia with Lewy bodies - Shu-hua LI; Kai LI; Hai-bo CHEN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2017)
DOI: 10.3969/j.issn.1672-6731.2017.01.001